AGRICULTURAL FARMS’ ADAPTATION AND ADJUSTMENT PROCESSES TO CHANGING ECONOMIC ENVIRONMENT IN POLAND (CASE STUDY OF ONE FARM) - Gradziuk, Barbara; Kłyż, Grzegorz (Acta Scientiarum Polonorum. Oeconomia, 2011)
The paper presents results of studies on the adjustment process of farms to market economy requirements. Trends of change were analyzed on the basis of a case study. The owner of the farm under analysis made significant changes in the farming production means and resources between 2005 and 2010, namely his actions showed a high tendency to concentrate land ownership. He also systematically invested in farming equipment and buildings, adapting their capabilities to the growing demands on farming requirements, organizational changes and technological developments. An important role in financing such activities was played by the supply of external capital, both in the form of preferential loans and EU funding and subsidies. The analysis of the farmer’s behaviour patterns ranks him as one of the most dynamic agricultural entrepreneurs, among the group of farmers who have sufficient resources to meet the demands of competition and stay in the market. They can act strategically, properly combining the internal potential with the opportunities created by the changing environment.